Diabetes distress and glycaemic control in young adults with type 1 diabetes: Associations by use of insulin pumps and continuous glucose monitors. Issue 11 (3rd August 2021) - Nagel, Kathryn E.; Dearth‐Wesley, Tracy; Herman, Allison N.; Smith, Hannah G.; Whitaker, Robert C.
Abstract: Aims: We determined whether high diabetes distress (DD) in young adults with type 1 diabetes was associated with higher glycated haemoglobin (HbA1c ) levels and whether this association was similar among those who were and were not using diabetes devices (insulin pumps and/or continuous glucose monitors [CGMs]). Methods: In 2017, an online survey was completed by 423 of 743 (57%) young adults (19–31 years) with type 1 diabetes receiving care at a specialty clinic in New York City. HbA1c level was the primary outcome measure, and high DD (Diabetes Distress Scale score ≥3) was the primary exposure. Associations were adjusted for sociodemographic covariates. Results: Of the 419 respondents with complete DD data, 59% were female and 69% were non‐Hispanic white. Both devices (pump and CGM) were used by 35%, either device by 42% and neither device by 24%. The mean (SD) HbA1c was 64 (19) mmol/mol (8.0 [1.7] %) and 24% had high DD. The adjusted mean (95% confidence interval) HbA1c was 10 (6, 14) mmol/mol (0.9 [0.5, 1.2] %) greater in those with high DD than in those without it. This HbA1c difference associated with high DD was similar regardless of device use: 9 (3, 15) mmol/mol (0.8 [0.3, 1.4] %) greater among those using both devices; and 9 (−0.9, 18) mmol/mol (0.8 [−0.1, 1.7] %) greater among those using neither device. Conclusions: High DD in young adults requires more attention because it is associated with higher HbA1c levels, even among those using insulin pumps and CGMs.